2021
DOI: 10.1101/2021.09.17.460671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the impact of gut microbiota on inflammation and hypertensive organ damage

Abstract: Aims: Hypertension (HTN) can lead to heart and kidney damage. The gut microbiota has been linked to HTN, although it is difficult to estimate its significance due to the variety of other features known to influence HTN. Methods and Results: In the present study, we used germ-free (GF) and colonized (COL) littermate mice to quantify the impact of microbial colonization on organ damage in HTN. Four-week-old male GF C57BL/6J littermates were randomized to remain GF or receive microbial colonization. HTN was induc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…45 Reintroduction of bacteria in germ-free mice was linked to increased anti-inflammatory SCFA production and attenuation of proinflammatory immune cell activation and organ injury, compared to germ-free mice, at baseline and following chronic Ang II infusion, this was more effective in the kidney than the heart. 46 Recently, it has been shown that SHR are immunoglobulin A deficient, which may contribute to the gut dysbiosis seen in this rat strain. 47,48 Together, this data shows dysbiosis may promote chronic inflammation and immune cell infiltration in tissues (heart, blood vessels, kidney, brain) to drive hypertension.…”
Section: Dysbiosis Inflammation and Hypertensionmentioning
confidence: 99%
“…45 Reintroduction of bacteria in germ-free mice was linked to increased anti-inflammatory SCFA production and attenuation of proinflammatory immune cell activation and organ injury, compared to germ-free mice, at baseline and following chronic Ang II infusion, this was more effective in the kidney than the heart. 46 Recently, it has been shown that SHR are immunoglobulin A deficient, which may contribute to the gut dysbiosis seen in this rat strain. 47,48 Together, this data shows dysbiosis may promote chronic inflammation and immune cell infiltration in tissues (heart, blood vessels, kidney, brain) to drive hypertension.…”
Section: Dysbiosis Inflammation and Hypertensionmentioning
confidence: 99%